Measurement of cortisol in blow samples collected from free‐swimming beluga whales (Delphinapterus leucas). Issue 3 (25th February 2021) - Hudson, Justine M.; Anderson, W. Gary; Marcoux, Marianne
Abstract: Blow or respiratory vapor collection is a noninvasive technique for monitoring the physiology of cetaceans and although this technique shows promise, a major challenge of blow collection is difficulty quantifying samples due to variable amounts of seawater contamination. Here, we aimed to (1) determine whether blow samples could be collected from free‐swimming belugas, (2) assess whether urea could be used as a dilution marker to normalize blow samples, and (3) determine which factors influenced cortisol and urea concentrations. We collected a total of 252 blow samples from free‐swimming belugas in the Churchill River in Manitoba, Canada. Cortisol, an indicator of individual stress and health, was detected in 65.87% of samples with concentrations ranging from 6.73 to 963.17 pg/ml of extract volume, while urea was detected in 90.48% of samples with concentrations ranging from 0.21 to 20.30 mg/L. We were unable to verify the efficacy of urea as a dilution marker to normalize blow samples from free‐swimming belugas; however, absolute cortisol concentrations varied based on sample device and quantity rating. Although we demonstrated that blow can be successfully collected from free‐swimming belugas, further refinement of this technique is needed before it can be used as a reliable method for physiological assessments.